The Correlation between Students' Learning Interest and Motivation and the Ability to Solve Problems in Online Learning IPA Subjects - Devi Rahmatul Aziza; Ria Wulandari (SEJ (Science Education Journal), 2020)
The purpose of this study was to describe the correlation between student’s learning interest and motivation with problem-solving abilities in online learning. This research was a quantitative correlation study. The population in this research was 7th-grade students of SMP 2 and the sample was 72 students. The instruments in this study consisted of three questionnaires, namely the questionnaire of student's learning interest, the questionnaire of student's learning motivation, and the questionnaire of problem-solving skills for daring learning. The data analysis technique used was simple and multiple linear regression tests. The results of this study indicated that there is a negative correlation between students' interest and motivation to learn simultaneously with problem-solving skills in distance learning but in the low category.